Guanylate Binding Proteins Enable Rapid Activation of Canonical and Noncanonical Inflammasomes in Chlamydia-Infected Macrophages - Finethy, Ryan (Infect Immun, 2015)
Interferon (IFN)-inducible guanylate binding proteins (GBPs) mediate cell-autonomous host resistance to bacterial pathogens and promote inflammasome activation. The prevailing model postulates that these two GBP-controlled activities are directly linked through GBP-dependent vacuolar lysis. It was proposed that the rupture of pathogen-containing vacuoles (PVs) by GBPs destroyed the microbial refuge and simultaneously contaminated the host cell cytosol with microbial activators of inflammasomes. Here, we demonstrate that GBP-mediated host resistance and GBP-mediated inflammatory responses can be uncoupled. We show that PVs formed by the rodent pathogen Chlamydia muridarum, so-called inclusions, remain free of GBPs and that C. muridarum is impervious to GBP-mediated restrictions on bacterial growth. Although GBPs neither bind to C. muridarum inclusions nor restrict C. muridarum growth, we find that GBPs promote inflammasome activation in C. muridarum-infected macrophages. We demonstrate that C. muridarum infections induce GBP-dependent pyroptosis through both caspase-11-dependent noncanonical and caspase-1-dependent canonical inflammasomes. Among canonical inflammasomes, we find that C. muridarum and the human pathogen Chlamydia trachomatis activate not only NLRP3 but also AIM2. Our data show that GBPs support fast-kinetics processing and secretion of interleukin-1β (IL-1β) and IL-18 by the NLRP3 inflammasome but are dispensable for the secretion of the same cytokines at later times postinfection. Because IFN-γ fails to induce IL-1β transcription, GBP-dependent fast-kinetics inflammasome activation can drive the preferential processing of constitutively expressed IL-18 in IFN-γ-primed macrophages in the absence of prior Toll-like receptor stimulation. Together, our results reveal that GBPs control the kinetics of inflammasome activation and thereby shape macrophage responses to Chlamydia infections.